Applying the total physical response (TPR) method to hone EFL students’ speaking skills - Alexon; Nina Kurniah; Nopri Pardianson (JOALL (Journal of Applied Linguistics and Literature), 2022)
This research aimed to describe the application of TPR method in improving understanding meaning and speaking skill and to describe the effectiveness of the application of TPR in improving student speaking skill in English subjects in class VII at SMPN 13 Bengkulu City. The method of research is used classroom action research and quasi-experiment. The subjects of class action research (CAR) are students of class VII A even semester in 2021/2022 at SMPN 13 Bengkulu City. The number of students in the CAR class is 25 people, the experimental class of VII B class is 25 people and the control class of VII C class is 25 students. The data collection method is using observation and tests, data analysis using the average score and t-test. The results showed that the application of the Total Physical Response (TPR) method can improve understanding meaning and speaking skill significantly that showed t count 5,30 > t table 2,064 then total physical response method can improve effectiveness of student speaking skill outcomes in the subject of English for class VII SMPN 13 Bengkulu City.